A waterborne outbreak of epidemic diarrhea due to group A rotavirus in Malatya, Turkey - Koroglu, Mehmet; Yakupogullari, Yusuf; Otlu, Baris; Ozturk, Serhat; Ozden, Mehmet; Ozer, Ali; Durmaz, Riza (Edizioni Int Srl, 2011)
We characterized an outbreak of acute diarrheal disease caused by group A rotavirus that occurred during the Autumn of 2005 in Malatya City Turkey A total 9907 patients between 0 to 91 years old (mean age: 25.05 +/- 19.67) were included in the epidemic. The patients' data were prospectively collected and statistically analyzed. Microbiologic analyses were performed to determine the etiologic agent. Rapid onset diarrhea (98.36%), abdominal cramps (69%), fever (44.4%) and vomiting (69.6%) were the most common symptoms observed in patients. Rotavirus antigen was detected in 52.7% of the studied patients. RT-PCR analysis led to identification of Group A rotavirus as the causative agent of this epidemic. Simultaneous measurements of the drinking water samples yielded very low chlorine levels; as low as 0 to 0.05 mg/L. The outbreak investigation team indicated possible contamination of a large water depository from a water well, which supplies drinking water to two major districts of the city Effective chlorination and blockage of the passage between the well and the water depository stopped the outbreak. This outbreak shows the high epidemic potency of rotavirus in large human populations, including all age groups, and underlines the importance of water safety in pipeline systems.
Keywords: Rotavirus; Outbreak; Waterborne; Diarrhea; Chlorination